Artikel Review: Efektivitas Mikroorganisme untuk Pengomposan Tandan Kosong Sawit secara Berkelanjutan - Legawati, Lisa; Maarasyid, Cici; Meldha, Zuqni; Liska, Salma; Yolanda, Yogi; Hendri, Yola Bertilsya; Ermal, Dini Aulia Sari; Elsa, Nesa Zafira (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Empty Fruit Bunches (EFB) of oil palm are the main solid waste generated by the palm oil industry, with an increasing volume and high lignocellulosic content that can affect the decomposition process. This article aims to review the effectiveness of various microorganisms as bioactivators in EFB composting based on experimental studies and recent literature. The review results indicate that using microbial consortia such as Trichoderma spp., cellulolytic bacteria, and local microorganisms (MOL) is more effective than single microorganisms in reducing the C/N ratio to levels approaching the compost quality standard (<20). Aerobic composting methods with proper aeration management and the addition of organic materials can also accelerate decomposition. Further research is recommended to examine the interactions among microorganisms within the consortia and to conduct application trials to validate the agronomic benefits of EFB compost sustainably.